THE RESEARCH OF MOTIVATION FOR LEARNING A FOREIGN LANGUAGE AMONG CADETS OF HIGHER MILITARY EDUCATIONAL INSTITUTIONS (MILITARY EDUCATIONAL UNITS AND HIGHER EDUCATION INSTITUTIONS) - Sameliuk, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The teaching of a foreign language in the system of higher education has a number of features due to the prospects of its use in the further professional activities of cadets, as well as professionally determined features of information perception and communicative aspects related to professional specialization. The formation of a high level of motivational attitudes to learning a foreign language has a clearly positive and even decisive impact on the success of learning a foreign language by cadets. The study of the process of teaching a foreign language (English) for cadets of non-linguistic specialties has a significant resonance in light of the prospects of Ukraine’s integration with the Euro-Atlantic partnership countries, as stated in the relevant government regulations. The purpose of the article was to study the current state of motivation to learn a foreign language among cadets of HEI’s non-linguistic specialties and develop a plan-prospectus for further control and formative impact on positive motivational attitudes of future servicemen in the process of learning a foreign (English) language to achieve a high level of competence (with a focus on the functional level of foreign language proficiency in accordance with NATO language standards STANAG 6001). 125 future servicemen were involved in the study. It was found that on average, a sufficient level of motivation to learn a foreign language prevails in the group of future military students. Thus, the majority of respondents (41.6 %) focused on a sufficient level of motivation, followed by a mediocre level of motivation (31.2 %), followed by one that needs significant improvement (10.4 %), a very good level (6.4 %), high (5.6 %) and critically low (4.8 %). Further work should be aimed at increasing very good and high levels of motivation. The next stage of the research should be the implementation of the generalized methods of stimulating motivation in learning English (through the active use of methods of personality-oriented learning) and checking the acquired level of motivation in a stable group of respondents of non-linguistic specialties.